2010
DOI: 10.1007/s10706-010-9337-1
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behaviour of Loose and Compacted Pond Ash

Abstract: Massive utilization of pond ash in earth works requires thorough understanding of its geotechnical characteristics, especially strength characteristics. Here in this paper, a detailed experimental study carried on the strength and other geotechnical characteristics of pond ash samples, collected from inflow and outflow points of two ash ponds in India, are presented. Strength characteristics were investigated using consolidated drained (CD) and undrained (CU) triaxial tests with pore water pressure measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The compression index of Panki and Panipat pond ash samples varies from 0.083 to 0.132 and 0.169 to 0.344 respectively. Comparing these results with the available data for pond ash reported by Jakka et al [12], it can be observed that Panki and Panipat pond ash shows higher compressibility value. …”
Section: Compressibility Characteristicssupporting
confidence: 77%
See 1 more Smart Citation
“…The compression index of Panki and Panipat pond ash samples varies from 0.083 to 0.132 and 0.169 to 0.344 respectively. Comparing these results with the available data for pond ash reported by Jakka et al [12], it can be observed that Panki and Panipat pond ash shows higher compressibility value. …”
Section: Compressibility Characteristicssupporting
confidence: 77%
“…Panipat pond ash shows little lower coefficient of permeability values as compare to Panki pond ash because of the presence of silt size particles. By comparing the present results with the results of pond ash reported by Jakka et al [12], it can be observed that Panki and Panipat pond ash shows little higher permeability value.…”
Section: Permeability Characteristicssupporting
confidence: 75%
“…Later, in several investigations, researchers have confirmed the suitability of coal ash as a construction material, especially for geotechnical applications because of its desirable engineering properties such as low specific gravity, good drainage, insensitive to water during compaction, low compressibility, and good frictional characteristics [10], [11]. Some other investigations on the use of coal ash in engineering practices, either by itself or blended with other soils/admixtures/inclusions reported the improvement in strength and stiffness characteristics [12]- [14].…”
Section: Fig 1 Schematic Diagram Of Model Rs Structurementioning
confidence: 99%
“…These shear strength values of the ash samples are provided in Table 1 along with the other geotechnical properties. Both the ash samples belongs to Class F category of ash and are non-plastic (Jakka et al 2010b).…”
Section: Selection Of Materials and Their Propertiesmentioning
confidence: 99%
“…In all these investigations, pond ash from inflow and outflow points of Badarpur ash pond is considered as construction material. Static strength characteristics and other geotechnical properties of these ash materials are presented in Jakka et al 2010b, while the cyclic strength characteristics of these materials are discussed in Jakka et al 2010a. The current article serves the final objective of the other two published articles, to find suitability of pond ash in the large geotechnical constructions and to evaluate their performance under seismic loading conditions.…”
Section: Introductionmentioning
confidence: 99%